A study of attitudes of mothers towards parent involvement in preschool centers - Yasa, E. Zeynep. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1996., 1996)
The present study aims to investigate the attitudes of mothers towards parent involvement in preschool education. This study attemps to answer the following two questions. Are there differences among mothers attitudes with respect to educational level of the mother, socioeconomic level of the school , age and sex of the child? What are the parent involvement activities in centers with different socioeconomic levels reported by the mothers and directors? The sample of the study was composed of 94 mothers whose children were between the ages of 3 to 6 years and attend preschool centers with different socioeconomic levels. Socioeconomic level of prescool centers were determined with respect to the amount of monthly fee paid per child to the center. Mothers in the sample were chosen from three different educational levels; high, middle and low. Educational level of the mothers was determined according to the school from which they had graduated. In addition to the mothers, 19 directors were chosen to find out the existing parent involvement activities in preschool centers with different socioeconomic levels. An interview schedule was constructed by the researcher. It included six subscales which are parent's involvement in noneducational school activities, information giving, parent's v involvement in their child's education, parent involvement 1n school education process, parent's involvement in school management and policy making and social links. The results for the total score which incorporated S1X subscales indicated no significant differences .in the attitudes of mothers with respect to their educational level. sex and age of their children and to the socioeconomic level of the school. On the other hand the results obtained from the subscalescores indicated significant differences for two of the subscales which are refered to "Parents' involvement 1n non-educational school activities" and "Parents' involvement in school management and policy-making". Mothers in the low and middle education group gave more importance to the above mentioned activities than the high education group. Both the parents and the directors reported that "Information giving" activities as existing in their centers. "Involvement in school management and policy-making" activities were reported as non-existent both by the mothers and the directors.
Keywords: Early childhood education -- Parent participation.